2016
DOI: 10.1108/rmj-08-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

A case study of records management practices in historic motor sport

Abstract: Pauline studies how information is perceived and used in organisations and communities. With this focus in mind, she completed her PhD at the University of Western Australia in 2011, studying how knowledge workers search for corporate information in electronic document and records management systems (EDRMS). Her PhD research is titled "EDRMS search behaviour: implications for records management practices". Pauline's current research interests are about the sustainability of communitybased information managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The research reported in this paper is part of continuing research by the author into the information management challenges of community archives and its sustainability in Australia using the motor sport community as a case study ( Joseph, 2015). First, this research investigated the information management practices at motor sport communitybased organisational levels at the historic car clubs, and the national and state offices of the Confederation of Australian Motor Sport (CAMS) Ltd (Joseph (2016)). Second, it investigated what are the motor sport community's significant information assets (records and archives) (Joseph (2016)) including what information individual motor sport enthusiasts required from CAMS (Joseph (Peer Review)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research reported in this paper is part of continuing research by the author into the information management challenges of community archives and its sustainability in Australia using the motor sport community as a case study ( Joseph, 2015). First, this research investigated the information management practices at motor sport communitybased organisational levels at the historic car clubs, and the national and state offices of the Confederation of Australian Motor Sport (CAMS) Ltd (Joseph (2016)). Second, it investigated what are the motor sport community's significant information assets (records and archives) (Joseph (2016)) including what information individual motor sport enthusiasts required from CAMS (Joseph (Peer Review)).…”
Section: Introductionmentioning
confidence: 99%
“…First, this research investigated the information management practices at motor sport communitybased organisational levels at the historic car clubs, and the national and state offices of the Confederation of Australian Motor Sport (CAMS) Ltd (Joseph (2016)). Second, it investigated what are the motor sport community's significant information assets (records and archives) (Joseph (2016)) including what information individual motor sport enthusiasts required from CAMS (Joseph (Peer Review)).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of recordkeeping practices in organisations run by volunteers are rare. Yet, as Joseph (2016, p. 330) wrote, many community groups face “considerable difficulties in capturing, managing and accessing their information assets”. Joseph (2015, 2016) studied recordkeeping practices in two historical motor‐sport community organisations in Australia, one being a national confederation with paid staff and the other one an affiliated club run by volunteers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, as Joseph (2016, p. 330) wrote, many community groups face “considerable difficulties in capturing, managing and accessing their information assets”. Joseph (2015, 2016) studied recordkeeping practices in two historical motor‐sport community organisations in Australia, one being a national confederation with paid staff and the other one an affiliated club run by volunteers. Like in the records management studies previously mentioned, her focus was to assess whether the recordkeeping practices of these organisations conformed to international standards.…”
Section: Literature Reviewmentioning
confidence: 99%